Cardiorespiratory fitness, visceral fat, and body fat, but not dietary inflammatory index, are related to C-reactive protein in cancer survivors. Issue 3 (September 2019) - Christensen, Matthew A; Smoak, Peter; Lisano, Jonathon K; Hayward, Reid; Coronado, Craig; Kage, Katie; Shackelford, Daniel; Stewart, Laura K
Background: The control of chronic inflammation has emerged as a target for improving the health of cancer survivors (CS). Aim: To examine differences in fitness and dietary characteristics of CS when grouped by low vs. moderate to high serum C-reactive protein (CRP). Methods: CS ( N = 26, mean age = 68 ± 12 years) were evaluated for body mass index (BMI), body composition, cardiorespiratory fitness, dietary intake, dietary inflammatory index (DII), and serum CRP. Participants were assigned to one of two groups based on serum CRP concentrations: low CRP (≤1 mg/L) (LWC; n = 13) or moderate to high (CRP > 1 mg/L) (MHC; n = 13) and t-tests compared them. Data are presented as mean ± SD. Results: LWC had higher VO2 peak values (mL/kg/min) ( p = 0.0003), and lower visceral fat area (cm 2 ) ( p = 0.02) and body fat mass (kg) ( p = 0.04). Secondary analysis using Pearson's correlation coefficients, including all current study participant data, found significant negative relationships between CRP and total dietary fat intake ( p = 0.02), saturated fat ( p = 0.03), and polyunsaturated fat ( p = 0.03). Conclusion: CS with moderate to high serum CRP concentrations had higher fat mass, visceral fat mass, and lower cardiorespiratory fitness. There was a significant negative relationship between dietary, fat, polyunsaturated and saturated fat, and CRP. However, these dietary fat related findings warrant further investigation. To summarize, improving cardiorespiratory fitness, maintaining lower body fat, may be helpful in altering chronic inflammation in CS.